50 years change in urban land use and ecological planning globally in the era of design with nature. Issue 1 (2nd January 2019) - Douglas, Ian
ABSTRACT: Ian McHarg's 1969 book, Design with Nature, was grounded in earlier good practice, especially the European vision of fitting cities into the regional landscape and carrying thorough surveys before planning commenced. The book emerged in the wake of publications that worried about the ability of the earth to support expanding populations and their growing impact on the environment. McHarg argued that ecological design should follow planning based on detailed site information. Although McHarg advised many urban authorities in the USA and other countries, especially in Africa, Asia and Europe, and his ideas had influenced some British new towns, they had little attention in the planning of Milton Keynes, England's largest new urban settlement, where the initial geological surveys were inadequate, but a successful large tree-planting program has created a "city in the forest." McHarg was however closely involved in planning the Nigerian Capital city, Abuja, but his sound master plan was ill-equipped to provide for a nation undergoing post-conflict rebuilding and a local population more concerned with access to land than ecological planning. Nonetheless, McHarg helped us to promote, protect, and preserve urban green spaces. Although teams from different disciplines now work well together, the integrated thinking advocated by McHarg remains sometimes in short supply in local practice.